2021
DOI: 10.1590/1980-57642021dn15-030013
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and balance dysfunctions due to the use of zolpidem in the elderly: a systematic review

Abstract: ABSTRACT. Zolpidem is one of the most widely prescribed hypnotic (non-benzodiazepine) agents for sleep disorder. Recently, an increase in the demand for this drug has been observed, mainly in the elderly population. Objective: This study aims to analyze the acute effect of zolpidem on cognitive and balance dysfunctions in the elderly population. Methods: A study was conducted by two independent researchers in four virtual scientific information bases and included randomized controlled trials. The studies eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…This NMA also reported that although no significant difference was noted in dropout due to adverse events between the eszopiclone and placebo groups, zolpidem and zopiclone had significantly more dropouts due to adverse events than placebo ( 13 ). Furthermore, previous studies have reported that NBZ was associated with side effects such as increased risk of falls ( 19 , 20 ), balance dysfunction ( 21 , 22 ), and increased risk of road traffic crashes, as noted with BZ ( 19 , 22 , 23 ). In addition, a study in Israel reported that NBZ was associated with an increased risk of long-term use of hypnotics compared with BZ ( 24 ).…”
Section: Discussionmentioning
confidence: 97%
“…This NMA also reported that although no significant difference was noted in dropout due to adverse events between the eszopiclone and placebo groups, zolpidem and zopiclone had significantly more dropouts due to adverse events than placebo ( 13 ). Furthermore, previous studies have reported that NBZ was associated with side effects such as increased risk of falls ( 19 , 20 ), balance dysfunction ( 21 , 22 ), and increased risk of road traffic crashes, as noted with BZ ( 19 , 22 , 23 ). In addition, a study in Israel reported that NBZ was associated with an increased risk of long-term use of hypnotics compared with BZ ( 24 ).…”
Section: Discussionmentioning
confidence: 97%
“…Esses medicamentos têm sido associados ao aumento na ocorrência de comprometimento cognitivo, delírio, acidentes automobilísticos, quedas e fraturas entre idosos. 4,5 Entre esses desfechos associados ao uso de sedativos benzodiazepínicos e drogas Z, as quedas e fraturas têm consequências consideráveis para os idosos, pois contribuem para a perda de confiança, quadros álgicos, redução da mobilidade, aumento da dependência, e até mesmo para a mortalidade desses indivíduos. Alguns estudos têm demonstrado o aumento das visitas aos serviços de emergência e internação hospitalar por quedas e fraturas de fêmur associado ao uso de benzodiazepínicos e drogas Z.…”
Section: Introductionunclassified